Deathstalker [videorecording (DVD)] - Kostanski, Steven; Bernhardt, Daniel; Orjalo, Christina; Lazenby, Paul (Actor); Rice, Nicholas (Actor) (Shout! Studios, 2026)
In a dark age of swords and sorcery, a wandering warrior discovers a powerful amulet that could decide the fate of a war-torn kingdom. Hunted by dark forces, he embarks on an epic quest battling monsters, magic, and his own past.